Evaluation of Nausea and Vomiting Severity in Pregnancies Conceived Through Assisted Reproduction - Ozge Senem Yucel Cicek; Merve Demir (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: This study aimed to evaluate the severity of nausea vomiting of pregnancy in assisted reproductive technologies pregnancies using the Pregnancy-Unique Quantification of Emesis scoring system which is a validated, clinically relevant method to assess nausea vomiting of pregnancy severity.